Stunting and its Risk Factors at Durenan Primary Public Healthcare in 2025 - Garnis Nirwanasari; Umi Nadhiroh; Fika Rohmawati (Riviera Publishing, 2026)
Stunting remains a major global health concern, particularly in low- and middle-income countries. Indonesia has successfully reduced its stunting prevalence over the past five years, reaching 19.8% in 2024. Stunting is caused by multiple direct and indirect factors, and nutritional deficiencies during the first 1,000 days of life, particularly the period from conception to two years of age, can have irreversible impacts on children’s growth and long-term quality of life. This study aimed to identify and analyze the risk factors associated with stunting among children in the working area of Durenan Primary Public Healthcare, Trenggalek Regency, and to provide baseline data on the prevalence of stunting in the region. This qualitative descriptive study used secondary data from 58 children with stunting aged 8–59 months in 2025, based on height-for-age <?2 standard deviations (SD) according to World Health Organization (WHO) standards. The study analyzed several risk factors, including maternal chronic energy deficiency, low household income, low birth weight, comorbidities, non-exclusive breastfeeding, exposure to cigarette smoke, and inadequate nutritional intake. Children without stunting were excluded from the analysis. Among the 58 children included in the study, 14 (24.13%) were born to mothers with chronic energy deficiency, 30 (51.72%) came from families with economic difficulties, 9 (15.51%) had low birth weight, 9 (15.51%) had comorbidities, 12 (20.68%) did not receive exclusive breastfeeding, 47 (81.03%) were exposed to cigarette smoke at home, and all children (100%) had inadequate nutritional intake. Stunting remains a significant public health challenge in Indonesia, particularly in rural areas. Prevention efforts should begin during preconception and continue throughout pregnancy and early childhood. Collaboration among healthcare professionals, healthcare facilities, and relevant sectors is essential to accelerate stunting reduction efforts and support the achievement of zero stunting in Indonesia.